Inhibition of breast cancer with transdermal tamoxifen-encapsulated lipoplex. Issue 1 (December 2016) - Lin, Yu-Ling; Chen, Chia-Hung; Wu, Hsin-Yi; Tsai, Nu-Man; Jian, Ting-Yan; Chang, Yuan-Ching; Lin, Chi-Hsin; Wu, Chih-Hsiung; Hsu, Fei-Ting; Leung, Ting; Liao, Kuang-Wen
Abstract Background Tamoxifen is currently used for the treatment of both early and advanced estrogen receptor (ER) positive breast cancer in pre- and post-menopausal women. However, using tamoxifen routinely to inhibit endogenous or exogenous estrogen effects is occasionally difficult because of its potential side effects. Objectives The aim of this study is to design a local drug delivery system to encapsulate tamoxifen for observing their efficacy of skin penetration, drug accumulation and cancer therapy. Methods A cationic liposome-PEG-PEI complex (LPPC) was used as a carrier for the encapsulation of tamoxifen and forming 'LPPC/TAM' for transdermal release. The cytotoxicity of LPPC/TAM was analyzed by MTT. The skin penetration, tumor growth inhibition and organ damages were measured in xenograft mice following transdermal treatment. Results LPPC/TAM had an average size less than 270 nm and a zeta-potential of approximately 40 mV. LPPC/TAM displayed dramatically increased the cytotoxic activity in all breast cancer cells, especially in ER-positive breast cancer cells. In vivo, LPPC drug delivery helped the fluorescent dye penetrating across the skim and accumulating rapidly in tumor area. Administration of LPPC/TAM by transdermal route inhibited about 86 % of tumor growth in mice bearing BT474 tumors. This local treatment of LPPC/TAM did not injury skin and any organs. Conclusion LPPC-delivery system provided a better skin penetration and drug accumulation and therapeutic efficacy. Therefore, LPPC/TAM drug delivery maybe a useful transdermal tool of drugs utilization for breast cancer therapy.